2005
DOI: 10.1084/jem.20042572
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of allergic airway inflammation by helminth-induced regulatory T cells

Abstract: Allergic diseases mediated by T helper type (Th) 2 cell immune responses are rising dramatically in most developed countries. Exaggerated Th2 cell reactivity could result, for example, from diminished exposure to Th1 cell–inducing microbial infections. Epidemiological studies, however, indicate that Th2 cell–stimulating helminth parasites may also counteract allergies, possibly by generating regulatory T cells which suppress both Th1 and Th2 arms of immunity. We therefore tested the ability of the Th2 cell–ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

38
561
1
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 572 publications
(604 citation statements)
references
References 74 publications
38
561
1
4
Order By: Relevance
“…Much the same is seen when other parasites replace T. spiralis as the co-infecting species and Table 3 summarises some of the studies that have shown this to be the case. Although the mechanism of this immunodepression is not fully understood it is likely to be based on immunomodulatory factors released by the worms that specifically depress components of the host response such as mastocytosis (Behnke et al 1992 ;Wilson et al 2005 ;Rzepecka et al 2006).…”
Section: The Immune Response As An E N V I R O N M E N T a L S T R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Much the same is seen when other parasites replace T. spiralis as the co-infecting species and Table 3 summarises some of the studies that have shown this to be the case. Although the mechanism of this immunodepression is not fully understood it is likely to be based on immunomodulatory factors released by the worms that specifically depress components of the host response such as mastocytosis (Behnke et al 1992 ;Wilson et al 2005 ;Rzepecka et al 2006).…”
Section: The Immune Response As An E N V I R O N M E N T a L S T R Ementioning
confidence: 99%
“…Other parasites alter the balance of the host's capacity to mount Th1 and Th2 responses or affect regulatory T cells (Wilson et al 2005). By initiating a Th2-driven response in the host, helminths may make the host more susceptible to concurrent infections that are better controlled by Th1 responses and vice-versa (Graham et al 2007 ;Graham, 2008).…”
Section: The Immune Response As An E N V I R O N M E N T a L S T R Ementioning
confidence: 99%
“…However, such effects can be beneficial by downregulating inflammatory reactions to allergens and inflammatory disorders of the intestinal tract. Studies in animal models showed that helminths can suppress airway hyperreactivity and colitis [6][7][8] and nematodes have been used to efficiently treat human inflammatory bowel disease in clinical trials [9,10]. …”
mentioning
confidence: 99%
“…It has been demonstrated that nematode infections may prevent and control undesired immune reactions [6][7][8][9][10][11][12]30]. Several studies showed that the beneficial effects of the infections could be mimicked by transfer of Treg derived from nematode-infected donors to naïve recipients rendering them refractory to the inflammatory disorders such as asthma and colitis [6,8,11,12]. These data indicate that circuits of Treg action during nematode infection may also modulate unrelated bystander immune reactions and supports the view of Treg as important immunoregulators that can be modulated by parasites.…”
mentioning
confidence: 99%
See 1 more Smart Citation